Malaria Falciparum in Pregnancy: A Case Series from an Endemic Area - Sentosa, I Gede; Kurniawan, Rommy Andika (Jurnal Kedokteran Brawijaya, 2024)
Malaria is a public health issue worldwide, especially in tropical areas such as Indonesia. Malaria in pregnant women leads to increased risks of anemia, low birth weight, and fetal death. In this study, we reported two cases of malaria in pregnancy in Sikka, East Nusa Tenggara, an endemic area, after several years with zero cases. The first case was malaria in the first trimester of pregnancy, while the second case was malaria with anemia and thrombocytopenia in the second trimester of pregnancy. Both patients were treated with supportive therapies and a combination of dihydroartemisinin-piperaquine (DHP) 1x3 tablets orally for three days, leading to a favourable outcome. Both cases showed that early diagnosis and combination therapy with the correct antimalarial agent is effective for malaria in pregnancy.